(untitled) (The Journal of Plant Protection Sciences, 2021)
The detection and identification of viruses has been a challenge since the advent of the discipline of plant virology over a century ago. A great variety of methods have been developed that permit differentiation of viral pathogens. These methods, initially based solely on identifying the distinct biological characteristics of different viruses, were soon supplemented with methods based on light or electron microscopy and serology and subsequently by Enzyme Linked Immunosorbant Assay (ELISA) and finally the use of molecular (nucleic acid-based) techniques have revolutionized the diagnosis of plant viruses. While the technologies available to virologists have obviously become more diverse and improved, the challenges have also changed greatly. Detection of plant viruses is becoming more critical as globalization of trade, particularly in horticultural commodities increase. The potential effects of climate change have further aggravated the movement of viruses and their vectors, transforming the diagnostic landscape.